Educational infrastructure and tax works in a political scenario of social profitability - Vizcarra Silvestre, Ronny Fernando (2021)
The improvement of educational infrastructure and tax works within the political scenario of social profitability, shows the private sector the tool to achieve a high level of perception of social responsibility. Where the objective is to determine if there is a relationship between tax works and the improvement of the educational infrastructure in each of its dimensions in times of social profitability. For this, the proposed methodology is the descriptive mode of non-experimental design of the correlational type with a quantitative approach. Where the result using the Rho Spearman symmetric measure of correlation indicates that there is a moderately high positive relationship of .614 with significance of p = 0.000> 0.05. This leads us to determine the existence of a positive relationship of the moderate level in high perception between both variables with a perception level of medium level in the academic, infrastructure and well-being dimensions of the variable Improvement of educational infrastructure. Concluding that the OxI help to consolidate the sustainable strategic alliance between the state, the private sector and the citizen, proposed as the Win-Win (Tec-Ww) collaborative success triangle.